2019
DOI: 10.1016/j.jcjo.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography-angiography in Wolfram syndrome: a mitochondrial etiology in disease pathophysiology

Abstract: Our patient had an extensive SCC of the medial eyelid involving most of the surrounding structures, making us consider an alternative for surgical treatment. In our opinion, topical immunotherapy should be tried before opting for a surgical excision, especially in difficult areas such as medial canthus, fornix extension, and elderly patients with systemic comorbidities. It has been proven to provide better cosmetic and functional outcomes without additional local morbidities (such as flaps or grafts). We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…118 The authors postulate a mitochondrial involvement related to the observed OCT-A findings. 117,118 Lesions of the Visual Pathway…”
Section: Wolfram Syndromementioning
confidence: 94%
See 2 more Smart Citations
“…118 The authors postulate a mitochondrial involvement related to the observed OCT-A findings. 117,118 Lesions of the Visual Pathway…”
Section: Wolfram Syndromementioning
confidence: 94%
“…A study by Asanad et al assessed the use of OCT-A in patients with Wolfram syndrome, rare neurodegenerative disease including diabetes insipidus, diabetes mellitus, deafness, and optic neuropathy. 117,118 The OCT-A demonstrated reduced blood flow of the radial peripapillary capillary plexus (RPC) and superficial capillary plexus (SCP), which correlated well with the corresponding RNFL thinning. 118 The authors postulate a mitochondrial involvement related to the observed OCT-A findings.…”
Section: Wolfram Syndromementioning
confidence: 98%
See 1 more Smart Citation
“…99,100 In addition, OCTA showed remarkable similarities between WS and LHON with respect to peripapillary telangiectatic blood vessels and vascular tortuosity (Figure 3 (b) and (e)), which are pathognomonic findings for LHON. 98,101 Future directions OCTA has served as a transformative tool for mapping vascular perfusion at the structural and qualitative functional levels. 17,102,103 In addition to structural indices of the retinal vasculature, retinal blood flow has also been recognized as a potentially valuable biomarker for neurodegenerative optic neuropathies.…”
Section: Doamentioning
confidence: 99%
“…OCTA images of the superficial capillary plexus (b, e) demonstrate visible attenuation of the temporal microvascular networks of the optic nerve head (ONH) and peripapillary area (red circle) along with peripapillary telangiectatic blood vessels and vascular tortuosity (red arrows) for the right (b) and left eyes (e). OCT cross-sections (c, f) overlaying retinal flow (red) on OCT reflectance (gray scale) show a perfusion defect associated with ONH (red arrow) and temporal peripapillary nerve fiber layer (orange arrows) for the right (c) and left (f) eyes from Asanad and colleagues 98.…”
mentioning
confidence: 95%